2012
DOI: 10.5120/8298-1917
|View full text |Cite
|
Sign up to set email alerts
|

Clustering the Preprocessed Automated Blood Cell Counter Data using Modified K-means Algorithms and Generation of Association Rules

Abstract: The raw data from an Automated Blood Cell Counter is transformed in to a Preprocessed and Flattened data using the preprocessing phases of the Knowledge Discovery in Databases and the transformed data is used to create clusters of the database in this paper. The K-Means algorithm is applied on the database to form various clusters. Twelve thousand records are taken from a clinical laboratory for processing. Associations among the various attributes of the database are generated. General TermsAlgorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The accuracy results of their experiments exceeded 90%, and it showed that the critical point which can be the first indicator of the thalassemia existence is MCV ≤ 77.65. Also, Minnie and Srinivasan in [11] used data mining on Blood Cell Counter data to convert the raw data into transformed data that can be used for generating knowledge. They used association rules and clusters on the collected data.…”
Section: Related Workmentioning
confidence: 99%
“…The accuracy results of their experiments exceeded 90%, and it showed that the critical point which can be the first indicator of the thalassemia existence is MCV ≤ 77.65. Also, Minnie and Srinivasan in [11] used data mining on Blood Cell Counter data to convert the raw data into transformed data that can be used for generating knowledge. They used association rules and clusters on the collected data.…”
Section: Related Workmentioning
confidence: 99%
“…[11] Automated Blood Cell Counter Data is clustered using the RBC attribute where the initial mean is selected as first k elements from the sorted ABCC data. [12] Genetic Algorithm (GA) and Entropy based fuzzy clustering (EFC) are used to assign k-means initial cluster centers for clustering PIMA Indian diabetic dataset. [13] …”
Section: Introductionmentioning
confidence: 99%